2022
DOI: 10.1002/pssa.202200316
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performance of InGaN/AlGaN Multiple‐Quantum‐Well Near‐UV Light‐Emitting Diodes with Convex Barriers and Staggered Wells

Abstract: The physical mechanism of improving the photoelectric performance of InGaN/AlGaN‐based near UV light‐emitting diode (LED) with convex quantum barrier and staggered quantum well (QW) is studied by numerical simulation. The simulation results indicate that the voltage–current characteristics of the LED structure with convex quantum barrier and staggered QW are effectively improved compared with the traditional multiple quantum well (MQW) structure, and its electroluminescence (EL) intensity and light output powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Figure 1 schematically describes the simulated MQW LED structure that involves GaN(n)/InxGa1-xN/GaN/AlGaN/GaN(p). Earlier studies, dealing with MQW structures were reported describing other aspects of the LED devices using the Atlas-Silvaco [40,42]. In the present study, a 3000 nm thick n-GaN layer is used.…”
Section: Structure Description and Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 schematically describes the simulated MQW LED structure that involves GaN(n)/InxGa1-xN/GaN/AlGaN/GaN(p). Earlier studies, dealing with MQW structures were reported describing other aspects of the LED devices using the Atlas-Silvaco [40,42]. In the present study, a 3000 nm thick n-GaN layer is used.…”
Section: Structure Description and Simulation Detailsmentioning
confidence: 99%
“…Therefore, simulation studies, using SilvacoTcad program [36], Matlab [37], Sentaurus [38] and Comsol metaphysics [39], were made. In fact, simulation helps understand the effects of various phenomena, such as radiative phenomena [40] and the band offset in quantum wells and barriers [41] on diode structures, optical properties and performance, while avoiding high production costs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] In addition, the optical recombination rate, Auger recombination coefficient, and Shockley–Read–Hall (SRH) recombination lifetime of electrons and holes are 10 −11 cm 3 s −1 , 2.88 × 10 −30 cm 6 s −1 , and 15 ns, respectively. [ 30,31 ] Second, considering the self‐shielding effect caused by the defect misalignment of the AlN template at the bottom of the actual DUV LED and the effect of interface charge compensation on the optical output power, the polarization effect was set as 50% of the total charge (there are more material parameters that were employed in the simulation. [ 32 ] ).…”
Section: Device Structures and Parametersmentioning
confidence: 99%